The Impact of the Covid-19 Pandemic on the Airline Firms Financial Performance: Evidence of Asean Countries - Kamal, Maulana; Maghfirah, Arini Geubri (Universitas Syiah Kuala, 2025)
Objective The purpose of this study is to examine the impact of the COVID-19 pandemic on the financial performance of airlines in ASEAN.Design/Methodology The population of this study consists of ASEAN airline companies whose reports are publicly accessible from 2019 to 2021. The sample population was obtained through a census sampling method, which resulted in the selection of 12 companies. The analysis employed a multifaceted approach, encompassing multiple linear regression analyses and a hierarchical regression strategy.Results Covid-19 pandemic had a negative impact on the financial performance of ASEAN airlines. An analysis conducted across six ASEAN countries (Malaysia, Indonesia, Singapore, Thailand, the Philippines, and Vietnam) reveals that airlines in Malaysia and Singapore had positive effect on their financial performance, while those in the other four countries faced a negative impact. These findings indicate that the effects of the COVID-19 pandemic on the airline financial stability were not uniform across all countries.Research limitations/implications The hypotheses of this study were analyzed using multiple linear regression, focusing solely on ASEAN airline companies that publish their financial reports. Additionally, the chosen methodology may not fully capture the long-term financial consequences of the pandemic on airline performance.Novelty/Originality This study is among the first empirical studies to analyze the financial impact of COVID-19 on the airline industry across multiple ASEAN countries. While previous research has primarily focused on global or country-specific analyses, this research provides a comparative perspective using financial data from six ASEAN nation.